2005
DOI: 10.1016/j.virol.2005.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Identification and preliminary characterization of vaccinia virus (Dryvax) antigens recognized by vaccinia immune globulin

Abstract: Using vaccinia immune globulin (VIG), a high-titer antibody preparation from immunized subjects, we demonstrate that the humoral immune response in humans is directed against numerous antigens in the Dryvax vaccine strain. Western blot and immunoprecipitation analyses revealed highly antigenic proteins associated with both the extracellular enveloped virus and intracellular mature virus forms. The modified vaccinia virus Ankara (MVA), a new generation smallpox vaccine that is attenuated for replication in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
50
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 36 publications
6
50
0
3
Order By: Relevance
“…In this assay, 95% (20/21) of monkeypox-immune participants (including 2/3 who had clinically inapparent cases) reacted with at least 1 diagnostic protein band. A cluster of 33 kDa-to 42 kDavaccinia proteins was previously described as immunoreactive with pooled human vaccinia immune globulin (27). This cluster was also evident in the current study (Figure 2, panels B and C), although detection and intensity of bands within this cluster varied among persons.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In this assay, 95% (20/21) of monkeypox-immune participants (including 2/3 who had clinically inapparent cases) reacted with at least 1 diagnostic protein band. A cluster of 33 kDa-to 42 kDavaccinia proteins was previously described as immunoreactive with pooled human vaccinia immune globulin (27). This cluster was also evident in the current study (Figure 2, panels B and C), although detection and intensity of bands within this cluster varied among persons.…”
Section: Discussionsupporting
confidence: 84%
“…Historically, several serologic techniques have been used to identify orthopoxvirus infections, including hemagglutination-inhibition (13), gel precipitation (17,22,23), complement fi xation (22), cross-neutralization (14), immunofl uorescence (24,25), Western blot (26,27), radioimmunoassay (13,15), and ELISA (28,29). In previous studies, we used a peptide-based ELISA with peptide sequences from the monkeypox B21R gene to differentially diagnose monkeypox infection (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that MVA does not produce all the major vaccinia proteins targeted by VIG [18]. These investigators determined one protein to be the vaccinia gene fragment corresponding to the cowpox A-type inclusion body.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of including A27L, D8L, and B5R as components of a subunit smallpox vaccine is underscored by the detection of antibody responses to both IMV-and EEV-associated proteins in the sera of humans immunized with Dryvax (25) or vaccinia virus strain Lister (36). Studies with nonhuman primates or mice have also demonstrated that immunization with baculovirus-expressed recombinant proteins or DNA vaccines composed of different combinations of IMV-and EEVassociated proteins-such as A33R, B5R, and L1R (14,15), A27L, A33R, L1R, and B5R (21), or A27L, B5R, L1R, A33R, and D8L (41)-result in the induction of high levels of neutralizing antibodies and in the protection of mice from lethal challenge with vaccinia virus.…”
mentioning
confidence: 99%